Efficacy and Safety of Skin Radiance Collagen on Skin and Hair Matrix: A Placebo-Controlled Clinical Trial in Healthy Human Subjects - Trehan A; Anand R; Chaudhary G; Garg H; Verma MK (Dove Medical Press, 2024)
Anupam Trehan, Rachna Anand, Garima Chaudhary, Himanshi Garg, Manoj Kumar Verma Bright Lifecare Pvt. Ltd, Gurugram, Haryana, IndiaCorrespondence: Rachna Anand, Bright Lifecare Pvt. Ltd, The Presidency, Tower B, Second Floor, 46/4, M G Road, Sector-14, Opp. Girls College, Gurgaon, Haryana, 122001, India, Email rachna.anand@brightlifecare.comPurpose: Collagen supplements are rising in the market as collagen has been demonstrated to be an important protein in the human aging process. Also, it is safe and easily absorbed in the body. Hence the aim of this study was to examine the effectiveness and safety of a collagen and antioxidant-rich treatment compared to a placebo in relation to various skin and hair indicators in healthy adult human subjects.Patients and Methods: Forty healthy adult non-pregnant/non-lactating women (aged 38- 50 years) provided their informed consent in writing before their participation. Skin Radiance Collagen (SRC) treatment and a placebo were assessed for efficacy before application on Day 1, and post-application on Days 28 and 56, to measure changes in skin elasticity, hydration, brightness, pigmentation; texture, wrinkles, dryness, smoothness, fine lines, changes in the crow's feet region; as well as hair strength and hair fall.Results: It was observed after 56 days that therapy with SRC, compared to placebo, produced a substantial effect on reduction of wrinkle depth and fine lines by 48.11% and 39%, respectively, with p-value < 0.01 in the test group. There was a 15.69% improvement in skin hydration observed and 28% reduction in hair fall with p-value < 0.01.Conclusion: SRC, a combination of collagen with hyaluronic acid (HA), biotin, and vitamins C and E, showed a significant improvement in skin and hair health, including improvements in skin elasticity, skin hydration, reduction in crow's feet area wrinkles and fine lines, hair fall, and decrease in roughness, leading to improved skin texture. Vitamin C in the formulation also acts as a collagen builder for the body and helps in preventing oxidative stress in the body. The test treatment SRC was found to be efficacious and safe in healthy human adult subjects.Keywords: skin hydration, skin roughness, hair fall reduction, crow's feet wrinkles, skin elasticity